Pengaruh Safety Climate dan Safety Leadership terhadap Safety Performance pada Pekerja Perusahaan Alat Berat Kalimantan Timur - Made Yenny Puspitarini; Tri Martiana (Media Gizi Kesmas, 2024)
Background: Maintaining and repairing heavy machinery in coal mines included significant danger and may result in mishaps. Even with management's best efforts to provide acceptable employment, policies, practices, infrastructure, and safety gear, property damage and small injury occurrences nevertheless happen. Objective: Examine how safety leadership and the safety environment affect employees of East Kalimantan heavy equipment companies' performance in terms of safety. Method: A questionnaire was utilized in the study to gather data from 65 respondents who were chosen by simple random selection. Results: The safety climate is positively and significantly impacted by safety leadership, according to path analysis (path coef = 0.962). Safety performance is positively and significantly impacted by safety leadership and climate (path coef = 0.562 and 0.415, respectively). With safety climate acting as a mediator, safety leadership may influence safety performance (path coef= 0.3992). Conclusion:  Safety leadership and safety climate can be antecedents for the safety performance of East Kalimantan heavy equipment company employees. Companies need to strengthen safety leadership by ensuring leaders practice safety principles, as well as creating a safety climate that is conducive to increasing employee safety commitment.